О возможности обогащения известняков класса 40-150 мм с использованием фотоэлектронного сепаратора - Шапорев, П. В.; Райко, Валентина Федоровна; Себко, Вадим Вадимович; Нечипоренко, Дмитрий Игоревич; Посторонко, А. И. (НТУ "ХПИ", 2010)
Laboratory researches by definition of possibility of limestone sorting by their color are carried out. The reflection factor is defined for different deposits. Relationship between the structure of mixes and their reflection factor value is established. The conclusion about enrichment possibility of limestone by its color to the standard requirements on carbonate raw materials is made.
Possibility of limestones concentrating in the class of 40-150 mm by the photoelectronic separator
Keywords: карбонатное сырье; коэффициент отражения; состав смеси; цветовой признак; limestone sorting; reflection factor